Effects of Mig Welding to Corrosion Behaviour of Carbon Steel - Nur Azhani, Abd Razak; Wai, Loon Ng; Juliawati, Alias (scientific.net, 2013)
This paper presents corrosion behaviour of welded low carbon steel at different welding parameters. Welding process was conducted using metal inert gas (MIG) technique at welding voltage range of 19 to 22 V with 1 V interval, and wire feed rate range of 90 to 120 inch per minute (ipm) with 10 ipm interval. Filler material used was ER 70S-6 with 1.2 mm diameter. Corrosion behaviour of welded carbon steel was tested using synthetic seawater environment with 3.5 wt% NaCl. Microstructure changes and penetration level of weldments were observed using scanning electron microscope (SEM). Results showed that, corrosion rate decreased when the welding voltage and wire feed rate increased with full penetration level of weldment attainment. The lowest corrosion rate occurred at the highest welding voltage and wire feed rate when full penetration of weldment occurred. From metallographic study, iron oxides and pitting was found on the surface of the exposed area after the corrosion test.